Case Report: Triphasic Waves in a 9-Year-Old Girl With Anti-NMDAR Encephalitis - Zhang, Ke; Xu, Shuang; Zhou, Yalan; Su, Tangfeng (Frontiers in Neurology, 2022)
Background: Triphasic waves (TWs) are mainly described in association with metabolic encephalopathy, especially hepatic encephalopathy. Now, as different conditions including non-metabolic and structural abnormalities have been reported to be associated with TWs, the presence of TWs becomes a non-specific finding for metabolic encephalopathy. Case Presentation: We report the first case of anti-NMDAR encephalitis in a 9-year-old girl presenting with TWs on EEG. The TWs background EEG lasted for about 12 hours on the 40th day of the disease course. No epileptic wave was found during a series of EEG examinations. The child was discharged from the hospital and no neurological sequelae remained after a six-month follow-up. Conclusions: TWs are not specific to metabolic encephalopathy, but can also occur in children with autoimmune encephalitis. This case achieved a good prognosis after the early initiation of immunotherapy.